2005
DOI: 10.1021/la0503552
|View full text |Cite
|
Sign up to set email alerts
|

A New Phase of the c(4 × 2) Superstructure of Alkanethiols Grown by Vapor Phase Deposition on Gold

Abstract: A self-assembled monolayer of dodecanethiol is grown onto (111) oriented gold by vacuum phase deposition and studied by ultrahigh vacuum scanning tunneling microscopy (STM). The films consist of domains that exhibit the c(4 x 2) over-structure of the hexagonal (square root of 3 x square root of 3)R30 of alkanethiols on gold. The domain size is only limited by the terrace size of the underlying gold. By higher resolution scans a new phase of the c(4 x 2) structure consisting of four inequivalent molecules that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 22 publications
(31 reference statements)
8
72
1
1
Order By: Relevance
“…o overlayer on Au(111) surfaces, which is further structured by a c(4×2) superstructure [16][17][18][19][20] that is readily observed by scanning tunneling microscopy (STM) with high-impedance tunneling junctions. 16,[21][22][23][24][25] Although many reports have described alkanethiol SAMs in the last 20 years, a full understanding of this system is far from complete, which is mostly due to the lack of understanding of imaging mechanism.…”
Section: Molecular Scale Images Reveal That Alkanethiol Sams Form a (mentioning
confidence: 99%
“…o overlayer on Au(111) surfaces, which is further structured by a c(4×2) superstructure [16][17][18][19][20] that is readily observed by scanning tunneling microscopy (STM) with high-impedance tunneling junctions. 16,[21][22][23][24][25] Although many reports have described alkanethiol SAMs in the last 20 years, a full understanding of this system is far from complete, which is mostly due to the lack of understanding of imaging mechanism.…”
Section: Molecular Scale Images Reveal That Alkanethiol Sams Form a (mentioning
confidence: 99%
“…The STM images of (2√3x3)rect. show significant variations, leading to suggestions for dodecylthiolate (n=12), for example, that this unit mesh may be associated with as many as five distinctly different structures [42]. However, there is evidence that artefacts of the technique associated with tip and imaging conditions are the cause of these differences [43], and that the images all correspond to only one (2√3x3)rect.…”
Section: Overviewmentioning
confidence: 99%
“…By use of nanometersized electrodes it was shown that direct electron transfer through the layer, rather than electron transfer at the defects, was dominant and that the size of the defects was 1-100 nm [261]. Indeed, the present consensus is that SAMs are collectively organized in different phases constrained by disordered boundaries and substrate defects [251]. The approach of Abbou et al [74] is also notableby use of the combined AFM-SECM technique they probed the structure and dynamics of polymer chains labeled on one end with a ferrocene unit and grafted on the other end to a gold surface.…”
Section: Self Assembled Monolayersmentioning
confidence: 96%
“…It is now well established that the complete monolayers formed on Au(111) adopt a commensurate (√3×√3)R30°structure, which is further structured by a c(4×2) superlattice. The superstructure is characterized by systematic arrangement of molecules with distinct height differences in STM images [250,251]. The alkane chain is tilted at 30°to the surface normal.…”
Section: Self Assembled Monolayersmentioning
confidence: 99%